Thermal simulator of 3D-IC with modeling of anisotropic TSV conductance and microchannel entrance effects - Chip-Hong Chang (2013)
This paper presents a fast and accurate steady state thermal simulator for heatsink and microfluid-cooled 3D-ICs. This model considers the thermal effect of TSVs at fine-granularity by calculating the anisotropic equivalent thermal conductances of a solid grid cell if TSVs are inserted. Entrance effect of microchannels is also investigated for accurate modeling of microfluidic cooling. The proposed thermal simulator is verified against commercial multiphysics solver COMSOL and compared with Hotspot and 3D-ICE. Simulation results shows that for heatsink cooling, the proposed simulator is as accurate as Hotspot but runs much faster at moderate granularity. For microfluidic cooling, our proposed simulator is much more accurate than 3D-ICE in its estimation of steady state temperature and thermal distribution.